PENGARUH MOTIVASI, PERILAKU BELAJAR, DAN KUALITAS PENGAJARAN TERHADAP HASIL BELAJAR MATA KULIAH PENGANTAR DASAR MATEMATIKA PADA MAHASISWA JURUSAN PENDIDIKAN MATEMATIKA IKIP PGRI BALI - Ni Kadek Rini Purwati (Emasains : Jurnal Edukasi Matematika dan Sains, 2016)
The Influence of Motivation, Learning Behavior, and the Quality of Teaching on Learning Outcomes of the Introduction to Basic Mathematics to Students Majoring in Mathematics Education IKIP PGRI Bali Introduction of basic mathematics is one of the elementary subjects for students majoring in mathematics education. As one of the basic subjects, sometimes students do not understand the contents of the lecture. Failure to achieve the desired target and the obstacles in the lecture caused by several factors, both originating from inside (internal) or outside (external) selfesteem, as well as the factor of learning approach. The aim of this research was to determine the influence of the quality of teaching, motivation and behavioral learning on learning outcomes of basic introductory math courses either simultaneously or partially. This study is a correlational study conducted at the students majoring in mathematics education on semester one at the IKIP PGRI Bali, with a sampling technique used was purposive sampling. The data were analyzed using multiple linear regression. Based on the analysis found that the quality of teaching, motivation and learning behavior simultaneously has no effect on learning outcomes of the course introduction to basic mathematics. However, only the motivation to learn have partially affect the learning outcomes of the course introduction to basic mathematics. Based on these results, the teaching faculty is expected to increase student motivation. Students are expected to participate actively in the learning process and encourage motivation in itself because of the presence of internal motivation within themself, then consciously thrust of these students will be the power to conduct learning activities.